2022
DOI: 10.1094/pbiomes-06-21-0038-r
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Stratification of Microbial Communities in Woody Plants

Abstract: Bacterial and fungal endophytes form diverse communities and contribute to the performance and health of their host plants. Recent evidence suggests that both host related factors and environmental conditions determine the community structure of plant endophytes. Yet, we know little about their distribution patterns, and underlying community assembly mechanisms across plant compartments. Here we analysed the structure of bacterial and fungal communities associated with tree compartments as well as their underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
1
7
1
1
Order By: Relevance
“…However, mixing samples from epicormic and crown branches should be avoided, because they are likely to represent different endobiome compositions. The greater richness found in the lower branches supports previous research (Andrews et al, 1980;Johnson and Whitney, 1989) and could be partly attributed to the high density of inoculum in the ground with ability of entering into the stems through roots, bark surface and stomata in leaves (Bahram et al, 2022). Similarly, as a substrate for fungi, epicormic shoots may differ in anatomy and vigor from proleptic shoots (Negrón et al, 2013).…”
Section: Within-tree Variation In Species Richness and Diversitysupporting
confidence: 80%
See 1 more Smart Citation
“…However, mixing samples from epicormic and crown branches should be avoided, because they are likely to represent different endobiome compositions. The greater richness found in the lower branches supports previous research (Andrews et al, 1980;Johnson and Whitney, 1989) and could be partly attributed to the high density of inoculum in the ground with ability of entering into the stems through roots, bark surface and stomata in leaves (Bahram et al, 2022). Similarly, as a substrate for fungi, epicormic shoots may differ in anatomy and vigor from proleptic shoots (Negrón et al, 2013).…”
Section: Within-tree Variation In Species Richness and Diversitysupporting
confidence: 80%
“…Numerous environmental factors can potentially affect plant colonization by endophytes, including age, light availability, spatial distance from soil, and microclimate within the crown (Johnson and Whitney, 1989;Helander et al, 1993;Bahram et al, 2022). The endophytic composition can be also affected by host geographical location and host vitality (Agostinelli et al, 2018).…”
mentioning
confidence: 99%
“…We found support for our first hypothesis, by finding that host‐related factors are the primary determinant of the community structure of MIB. This finding corroborates the results of several local‐scale studies (Benucci and Bonito, 2016; Pent et al ., 2017; Gohar et al ., 2020) and is in agreement with those reporting that plant‐associated microbial communities are more strongly influenced by host phylogeny and identity compared to environmental factors (Põlme et al ., 2013; Tedersoo et al ., 2013; Yang et al ., 2019; Bahram et al ., 2021a). Other studies on animal gut microbiomes have also reported a strong effect of host genotype and diet rather than geographic location and environmental conditions on microbial community structure, in chimpanzees (Bueno de Mesquita et al ., 2021), humans (Yatsunenko et al ., 2012) and sponges (Thomas et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…attenuatus–lecanii–muscarius complex, have not yet been found as endophytes in local trees (Küngas et al, 2020 ), including Betula spp. (Bahram et al, 2021 ) with very few records from soil samples in the area (Tedersoo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%